2005
DOI: 10.1089/pho.2005.23.251
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Helium-Neon Laser Irradiation on Normal and Wounded Human Skin Fibroblasts

Abstract: A dose of 10 J/cm2 appeared to produce a significant amount of cellular and molecular damage, which could be an important consideration for other therapies, such as photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 11 publications
8
65
0
6
Order By: Relevance
“…The results support findings from Hawkins and Abrahamse [33], which reported that 5 J/cm 2 using 632.8 nm stimulates mitochondrial activity, cell proliferation, and migration to accelerate wound closure [33]. However, wounded cells exposed to 5 J/cm 2 using 632.8 nm in IR show an increase in caspase 3/7, increase in cytotoxicity, and decrease in viability when compared to cells exposed in the dark or in the light indicating an undesirable thermal effect of IR light.…”
Section: Resultssupporting
confidence: 91%
“…The results support findings from Hawkins and Abrahamse [33], which reported that 5 J/cm 2 using 632.8 nm stimulates mitochondrial activity, cell proliferation, and migration to accelerate wound closure [33]. However, wounded cells exposed to 5 J/cm 2 using 632.8 nm in IR show an increase in caspase 3/7, increase in cytotoxicity, and decrease in viability when compared to cells exposed in the dark or in the light indicating an undesirable thermal effect of IR light.…”
Section: Resultssupporting
confidence: 91%
“…1 It is broadly applied to reduce inflammation, 2 promote tissue regeneration, 3 relieve pain 4 enhance healing process of wound 5,6 and increase cell proliferation. 7,8 The molecular mechanisms of biological responses after LLL exposure have not been fully demonstrated. It is believed that physiological effects induced by LLL depend on the absorption of energy by some molecular photoacceptors or chromophores in the target cells.…”
Section: Introductionmentioning
confidence: 99%
“…For wound healing type studies, these cells are likely to be endothelial cells, 7 fibroblasts, 8 keratinocytes, 9 and possibly some classes of leukocytes. 10 Corneal epithelial repair involves a multifaceted series of events with specific physiologic functions.…”
Section: Discussionmentioning
confidence: 99%